The Impact of Knowledge Management Processes in Improving The Quality of Decisions in The Palestinian Ministry of Finance - The Southern Governorates - Abu Aisha, Mahmoud Mohammed; Ashour, Yousif Hussein; Al-Slakhi, Haytham Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aims at clarifying the real quality of decisions and the level of knowledge management of the Palestinian Ministry of Finance in the southern governorates, to determine the impact of knowledge management on the quality of decision-making and to show the impact of each knowledge management process (knowledge acquisition, knowledge storage, knowledge sharing, knowledge application) on the quality of decisions of the Palestinian Ministry of Finance in the southern governorates, and that is in light of the clear insufficiency of previous studies in addressing the subject of the study, also the previous studies have proven the existence of problems that hinder the decision-making process, all of the previous expresses the problem of the study and its importance. The study hypotheses are represented in the first main hypothesis: There is a statistically significant effect at a significance level (α ≤ 0.05) of knowledge management dimensions on the quality of decisions in the Palestinian Ministry of Finance in the southern governorates, and the second main hypothesis: There are differences in the average responses at a significance level (α ≤ 0.05) regarding knowledge management in the Palestinian Ministry of Finance in the southern governorates attributed to the following personal and organizational variables: (academic qualification, years of service, administrative level, program), and  the third main hypothesis: There are differences in the average responses at a significance level (α ≤ 0.05) regarding the quality of decisions in the Palestinian Ministry of Finance in the southern governorates attributed to the following personal and organizational variables: (academic qualification, years of service, administrative level, program). The analytical descriptive method was adopted. The study population consisted of all the Palestinian Ministry of Finance supervisory staff in the southern governorates of (281) staff, where the comprehensive survey method was used, and questionnaires were distributed to all staff, where (209) questionnaires were tested and were considered valid.